Transurethral Retrograde Fishing the Double J Urethral Stent: A Tertiary Children Hospital's Experience With a New Technical Strategy - Yu, Chengjun; Wei, Chun; Dong, Junjun; He, Xingyue; Wei, Yi; Wen, Sheng; Lin, Tao; He, Dawei; Wu, Shengde; Wei, Guanghui (Frontiers in Pediatrics, 2022)
Purpose The purpose of this study is to provide a new strategy for non-cystoscopic double J urethral stent (JJS) removal, the transurethral retrograde fishing the double J urethral stent (TURFJJS), that avoids general anesthesia in pediatric populations. Methods We retrospectively reviewed the JJS removal records of patients having ureteropelvic junction obstruction (UPJO). We analyzed differences in the removal success rates, operation-related severe complications, total cost, duration, and parental satisfaction between TURFJJS and traditional cystoscopic double J urethral stent removal (CJJSR) procedures. Results A total of 324 patients with UPJO were included in this study. CJJSR yielded a success rate of 100%. TURFJJS achieved a success rate of 94.3%. The TURFJJS was just an outpatient procedure, and its total cost was about 800 Chinese yuan (US$ 124). There were no severe JJS removal-related complications using TURFJJS. Parental satisfaction was 98.2 and 92.5% for the CJJSR and TURFJJS protocols, respectively. Conclusion TURFJJS is safe, effective, cost-effective, and well-tolerated in pediatric patients, minimizing or eliminating the need for general anesthesia, additional hospitalization, and waste of time. TURFJJS should be widely used in pediatric urology.